The Influence of Human Resource Competency, Work Environment and Work Ability on PT Employee Performance. Kendari Maritime Gifts - Supriaddin, Nofal; Samdin, Samdin; Fadhila, Neno (International Journal of Management and Education in Human Development, 2024)
In order to achieve a perfect level of success, every company must improve the quality of its resource management. Human resources are an important asset in the progress and development of a company. Basically, the most important thing to achieve a maximum goal is to start from the thing that most supports the achievement of that goal, namely human resources (HR). So it is necessary to carry out something called management or development which aims to create productive humans. With good human resource development or management, an employee can easily face and complete task demands both now and in the future. As time goes by, achievements and skills will be difficult for an employee to obtain if they only rely on what they have without ever carrying out a training or development process. PT. Kurnia Bahari Kendari is a company operating in the shipping, expedition and logistics distribution sector. Facing competition with many competitors in the same field certainly requires PT. Kurnia Bahari Kendari continues to improve the HR competency of its employees, creates a conducive work environment and employees' work abilities must always be honed in order to be able to compete in this business field. The phenomenon that occurred found that there were still some employees who had low competence and inadequate work abilities, especially field employees. Apart from that, field employees should also be required to continue to develop their abilities so that their performance continues to improve. Based on this, this research aims to 1. Test and analyze the influence of HR competency, work environment and work ability on the performance of PT employees. Kendari Maritime Gifts. 2. Test and analyze the influence of HR competency on PT employee performance. Kurnia Bahari Kendari 3. Test and analyze the influence of the work environment on the performance of PT employees. Kurnia Bahari Kendari 4. Test and analyze the influence of work ability on the performance of PT employees. Kendari Maritime Gifts. This research is associative research, namely research that aims to determine the influence or relationship between two or more variables.The research results show that HR competency, work environment, and work ability simultaneously have a significant influence on employee performance. In other words, these three variables function synergistically in influencing employee performance. An increase in one or more of these variables can lead to increased employee performance, while a decrease in these variables can result in a decrease in performance. Specifically, HR competency is proven to have a significant influence on employee performance; The higher the HR competency, the better the employee performance. HR competencies include the skills, knowledge and abilities possessed by employees, which directly influence the effectiveness and results of their work. However, the work environment only shows a positive but not significant influence on employee performance, indicating that although there is a positive relationship, this relationship is not strong enough to be considered significant in the context of this study. These findings provide insight into the factors that contribute to improving employee performance and can be used as a basis for HR development strategies in companies.